How strong is strong enough? - Moir, G. (coachesinfo.com)
Most coaches and athletes would agree that in sports such as weightlifting and particularly powerlifting, continuous increases in maximum strength would be advantageous. However, there is no agreement with regard to how strong athletes in other sports need to be. The purpose of this discussion is to describe the relationship between strength and 1) sports performance and 2) other variables contributing to athletic performance, particularly rate of force development and power. The discussion will be divided into two parts. Part One will deal with sports more oriented toward strength and power production and Part Two will consider sports requiring great endurance.